2022
DOI: 10.1101/2022.08.02.502485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential anti-monkeypox virus activity of atovaquone, mefloquine, and molnupiravir, and their potential use as treatments

Abstract: Monkeypox virus (MPXV) is a zoonotic orthopoxvirus that causes smallpox-like symptoms in humans and caused an outbreak in May 2022 that led the WHO to declare global health emergency. In this study, from a screening of approved-drug libraries using an MPXV infection cell system, atovaquone, mefloquine, and molnupiravir exhibited anti-MPXV activity, with 50% inhibitory concentrations of 0.51-5.2 microM, which is more potent than cidofovir. Whereas mefloquine was suggested to inhibit viral entry, atovaquone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In a study, Atovaquone was used in conjunction with other recognized antiorthopoxvirus medications such as tecovirimat. It is worth noting that the combination of tecovirimat and atovaquone reduced the levels of MPXV DNA in cell culture tests while having no negative effects on the cells themselves 161 …”
Section: Monkeypox Therapeutic Drug Targets and Strategiesmentioning
confidence: 96%
See 2 more Smart Citations
“…In a study, Atovaquone was used in conjunction with other recognized antiorthopoxvirus medications such as tecovirimat. It is worth noting that the combination of tecovirimat and atovaquone reduced the levels of MPXV DNA in cell culture tests while having no negative effects on the cells themselves 161 …”
Section: Monkeypox Therapeutic Drug Targets and Strategiesmentioning
confidence: 96%
“…According to a study, the levels of intracellular MPXV DNA were decreased by atovaquone, leflunomide, and teriflunomide (DHODH inhibitors) in a dose‐dependent manner. It was demonstrated that inhibiting DHODH prevented the reproduction of the MPXV 161 …”
Section: Monkeypox Therapeutic Drug Targets and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro screen of 132 clinically approved drugs identified atovaquone, mefloquine, and molnupiravir with efficacy against MPXV. 52 Supportiveandsymptomaticcare,whichmaybetheonlyresources availableforpatientsinresource-limitedsettings,playanimportantrole in the management of monkeypox. Pain management is key and requires topical agents, oral medications, or nerve blocks.…”
Section: Managementmentioning
confidence: 99%
“…An in silico study has shown better efficacy against mpox virus with combination of atovaquone and TPOXX (Akazawa et al, 2022). Some of the common associated adverse events are headaches, gastrointestinal disturbances, and injection site complaints like pain, swelling, erythema and extravasation (De Clercq et al, 2022;Food and Drug Administration, 2022;Siegrist and Sassine, 2022).…”
Section: Treatments and Vaccinesmentioning
confidence: 99%